Prevalence of supernumerary teeth in permanent dentition among patients attending a dental college in South Kerala: A pilot study - Devi Gopakumar; Jincy Thomas; Prasanna Ranimol; Daniel Alex Vineet; Sunila Thomas; Vivek Velayudhan Nair (Wolters Kluwer Medknow Publications, 2014)
Background: Supernumerary teeth are excess number of teeth formed as a result of disturbances occurring during odontogenesis. The objective of the study was to investigate the prevalence of supernumerary teeth in permanent dentition among patients attending a dental college in South Kerala. Materials and Methods: In this study, 11,141 subjects attending the out-patient department of PMS College of Dental Science and Research, Thiruvananthapuram, Kerala were examined for supernumerary teeth like mesiodens, paramolars, distomolars, third premolars, second laterals, and odontomes during the period May 2012-May 2013. Ethical clearance was obtained from the institutional ethical committee for the study. Results: The study showed a prevalence of 0.39% and a sex distribution of M:F equal to 2:1. The incidence of supernumerary teeth found was as follows: mesiodens (0.14%), paramolars (0.13%), third premolar (0.04%), distomolar (0.03%), extralateral (0.02%), and odontome (0.03%). The male:female gender predilection was as follows: mesiodens (3:1), paramolars (1.3:1), third premolar (4:1), distomolar (1:2), and odontome (2:1). Conclusion: This study showed a 0.39% prevalence of supernumerary teeth in this population.